2022
DOI: 10.33160/yam.2022.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bacteria from Spoiled Bottled Salad Dressing Leading to Gas Explosion

Abstract: Background In 2020, an incident involving spoiled salad dressing from a commercial source occurred. Upon opening the bottle, the contents exploded from gas that seemed to have fermented inside the bottle. For safety concerns, we sought to investigate the bacteria from the salad dressing in order to notify the company that made the product and relevant authorities. Methods Anaerobic and carbon dioxide culture methods were used. To determine species of colonies, MALDI-TOF-MS and 16S rRNA whole sequencing were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…The microorganism identified in the sequence obtained was Bacillus clausii with 96% identity for the sequenced fragment. It has been found that some strains of Bacillus clausii can grow in anaerobic conditions [42] and have been isolated from various environments, usually found in soils, marine soils [43,44], and biofilms of corroding environments [45]. Although this was the only identified microorganism, the consortium was made up of various types of microorganisms, determining that a highly reducing environment requires protection for the consortium.…”
Section: Isolation and Identificationmentioning
confidence: 99%
“…The microorganism identified in the sequence obtained was Bacillus clausii with 96% identity for the sequenced fragment. It has been found that some strains of Bacillus clausii can grow in anaerobic conditions [42] and have been isolated from various environments, usually found in soils, marine soils [43,44], and biofilms of corroding environments [45]. Although this was the only identified microorganism, the consortium was made up of various types of microorganisms, determining that a highly reducing environment requires protection for the consortium.…”
Section: Isolation and Identificationmentioning
confidence: 99%